Effects of renewable fuel and exhaust aftertreatment on primary and secondary emissions from a modern heavy-duty diesel engine. (August 2021) - Gren, Louise; Malmborg, Vilhelm B.; Falk, John; Markula, Lassi; Novakovic, Maja; Shamun, Sam; Eriksson, Axel C.; Kristensen, Thomas B.; Svenningsson, Birgitta; Tunér, Martin; Karjalainen, Panu; Pagels, Joakim
Abstract: Compared to petroleum diesel, renewable diesel fuels and exhaust aftertreatment systems can reduce primary exhaust emissions that are hazardous to human health and the environment. Secondary aerosol emissions which form upon atmospheric processing have, however, been less studied. This study aimed to quantify the impacts of replacing petroleum diesel with renewable fuels (hydrotreated vegetable oil [HVO] and rapeseed methyl ester [RME]) on primary and secondary aerosol emissions from a heavy-duty diesel engine at different stages of an exhaust aftertreatment system. Emission characterization was obtained by combining a battery of physical characterization techniques with chemical characterization using aerosol mass spectrometry. At engine-out measurements, RME and HVO reduced primary particulate matter (PM) emissions (for example equivalent black carbon [eBC]) and secondary aerosol production (studied with an oxidation flow reactor [OFR]) by mass compared to petroleum diesel. The diesel oxidation catalyst (DOC) reduced primary nucleation mode emissions, reduced the effective density of soot mode emissions, and reduced secondary particle production by mass. The DOC + a diesel particulate filter removed >99% of the particle number and eBC emissions. Volatile PM emissions (for example organic aerosol) were found to be distributed between the nucleation mode and soot mode for both primary and secondary emissions, to a degree that depends on both fuel type and aftertreatment. A high mass concentration of condensable species and a low condensation sink in the soot mode led to increased fractions of condensable species present in the nucleation mode. Aging in the OFR led to increases in particle effective density. Motoring the engine (running without combustion) showed that the nucleation mode originated primarily from lubricating oil, and nonvolatile nanoparticle emissions were identified down to 1.2 nm in particle size. In conclusion, replacing petroleum diesel with HVO and RME changes emission characteristics and can help reduce key aerosol emissions of relevance for adverse health and climate impact, especially for diesel engines with no or limited exhaust aftertreatment. Highlights: Use of RME or the DOC decreased the gas phase hydrocarbons by around 70%. The combination of DOC + DPF reduced eBC and particle number concentration by >99%. The nucleation mode particles, measured down to 1.2 nm, originated from the lubricant. Secondary aerosol formation was significantly lower for RME and HVO compared to diesel. The secondary aerosol formation was low for all fuels after the DOC.